Connections and gateways: the Pretoria Interchange - Teague, Gareth Bernard (My University, 2012)
The implementation of new public transport networks, such as the Gautrain, present new responsibilities and opportunities for urban development. Mega projects like these are constructed for various economical, social and political reasons. These underlying orders beg a necessary question when defining the architectural program required for the integration of the stations and there relative contexts. Integration is a key narrative for the exploration and enquiry of this thesis. The new Gautrain system should connect with existing and future transport systems, social systems and other contextual realities. Another question raised throughout the theoretical enquiry of this thesis is; to what extent does this connection and integration occur at the recently completed Gautrain stations? The idea of creating ‘Gateways’ into a city, rather than mere station ‘posts’ is explored as an architectural narrative. These ‘Gateways’ become the introductory point for commuters and an opportunity to create an experiential dimension relating to ‘the image of a city’ and its ‘zeitgeist’. Pretoria Station was chosen due the many layers of integration intrinsic to the site. This opportunity is available due to the existence of neo‐classical buildings within the immediate and macro context. Here the application of a contemporary, 21st century piece may create a representation of the progression of architectural and sociological thinking, relating to city building and transportation. This site also offers opportunities for exploring the integration of existing and future transport networks due to the existence of several of transport modes. Theories of city building and ‘placemaking’ are explored as a requirement borne out of the neglect for this site as it has developed through the modern era.
Keywords: Gautrain Transport interchange Transport networks Public transport